Aluminum fin material and frost inhibitor

The aluminum fin material with an amphoteric polylysine derivative coating addresses icing and frost issues in heat exchangers by delaying ice nucleation and enhancing hydrophilicity, ensuring efficient heat exchange and durability.

JP7609712B2Active Publication Date: 2025-01-07KOBE STEEL LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021095449
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-07
Publication Date
2025-01-07
Estimated Expiration
2041-06-07

AI Technical Summary

Technical Problem

Existing heat exchanger fin materials face issues with icing and frost formation, which reduce heat exchange efficiency and require defrosting operations, and existing solutions for hydrophilicity and water repellency have durability concerns.

Method used

An aluminum fin material with a coating layer containing an amphoteric polylysine derivative, optionally combined with crosslinking agents and surfactants, to form an icing and frost suppressing film that delays ice nucleation and enhances hydrophilicity.

Benefits of technology

The solution effectively suppresses icing and frost formation, maintaining heat exchanger efficiency by delaying frost formation and improving hydrophilicity, with enhanced durability and compatibility with additional film layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609712000012
    Figure 0007609712000012
  • Figure 0007609712000013
    Figure 0007609712000013
  • Figure 0007609712000001
    Figure 0007609712000001
Patent Text Reader

Abstract

To provide an aluminum fin material having an icing / frosting suppression coating layer with an excellent icing / frosting suppression effect.SOLUTION: An aluminum fin material has an aluminum plate and a coating layer formed on the surface of the aluminum plate, and the coating layer comprises an icing / frosting suppression coating layer containing an amphoteric polylysine derivative.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum fin material, and in particular to an aluminum fin material suitable for use in a heat exchanger of an air conditioner, etc. The present invention also relates to an anti-frost agent that can be applied to the aluminum fin material. [Background technology]

[0002] Heat exchangers are used in a variety of products, including room air conditioners, packaged air conditioners, freezer showcases, refrigerators, oil coolers, and radiators. Aluminum and aluminum alloys, which have excellent thermal conductivity, workability, and corrosion resistance, are generally used as materials for heat exchanger fins. Plate fin and plate and tube heat exchangers have a structure in which fin materials are arranged in parallel at close intervals.

[0003] When the surface temperature of the fin material of a heat exchanger falls below the dew point, condensed water adheres to it. If the surface of the fin material is not hydrophilic, the contact angle of the condensed water increases, causing it to splash around in the living environment, a phenomenon known as water splashing. When the condensed water combines and grows large, it forms a bridge between adjacent fin materials, blocking the ventilation passage between the fin materials and increasing ventilation resistance. For the purpose of preventing such water splashing and reducing ventilation resistance, for example, Patent Document 1 proposes a technique of applying and forming a hydrophilic coating on the surface of the fin material.

[0004] On the other hand, when the air conditioner is operated in heating mode, the surface temperature of the heat exchanger falls below the freezing point, and the condensed water on the surface of the fin material turns into frost or ice, resulting in frost formation. If the hydrophilicity is made too high, the frost formation becomes more likely to occur. If the fin material is blocked by the frost formation, the heat exchange efficiency of the heat exchanger is significantly reduced, and defrosting operation, etc. is required.

[0005] Therefore, various techniques for suppressing the formation of ice and frost on fin materials have been studied. For example, Patent Document 2 discloses that fluoroalkoxysilane with a critical surface tension of 20 dyn / cm or less is chemically adsorbed on the surface of the air-side heat transfer surface, and a coating having a structure in which CF3 groups are oriented on the outermost surface is formed, thereby imparting high water repellency and making the formation of frost less likely to occur. Patent Document 3 also discloses that a water-repellent coating is formed on the surface and the surface average roughness Ra is set to 20 μm or more, thereby reducing the area of ​​water droplets (snow, ice) and reducing their adhesive force.

[0006] However, there are concerns that the water repellency may deteriorate over time, and that the durability may decrease due to a decrease in the strength of the water repellent coating when the average surface roughness Ra is increased. Therefore, Patent Document 4 discloses a heat exchanger having a first layer and a second layer located closer to the air than the first layer as a heat transfer part, the second layer being composed of a polymer layer having a plurality of polymer chains, and the roots of the main chains of adjacent polymer chains on the first layer side being bonded to each other by a metal oxide network structure. According to this, the polymer chains of the second layer can be bonded at high density in the direction perpendicular to the first layer, so that the hydrophilicity of the surface of the heat transfer part can be reliably improved, and even if condensed water occurs on the surface of the heat transfer part, the growth of frost can be sufficiently delayed. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 2520308 [Patent Document 2] Japanese Patent Application Publication No. 10-281690 [Patent Document 3] Japanese Patent Application Publication No. 9-228073 [Patent Document 4] JP 2019-158247 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, no specific consideration has been given to the suppression of icing and frost formation for the heat exchanger in Patent Document 4. In addition, it cannot necessarily be said that improved hydrophilicity improves the suppression of icing and frost formation, and a separate test is required to suppress icing and frost formation.

[0009] The present invention aims to provide an aluminum fin material having an icing / frost-suppressing coating layer that is highly effective in suppressing icing / frost, and also aims to provide an icing / frost-suppressing agent that is highly effective in suppressing icing / frost. [Means for solving the problem]

[0010] The present invention relates to the following [1] to [7]. [1] An aluminum fin material having an aluminum plate and a coating layer formed on a surface of the aluminum plate, the coating layer comprising an anti-frost coating layer containing an amphoteric polylysine derivative. [2] The aluminum fin material according to [1], wherein the anionic group of the amphoteric polylysine derivative has the following structure in a side chain:

[0011] [ka]

[0012] (In the formula, R represents a direct bond or a linear or branched alkylene group having 1 to 5 carbon atoms.)

[0013] [3] The aluminum fin material described in [1] or [2] above, wherein the anti-frost coating layer further contains a cross-linking agent. [4] The aluminum fin material according to any one of [1] to [3], wherein the coating layer further comprises at least one selected from the group consisting of a corrosion-resistant coating layer, a hydrophilic coating layer, and a lubricating coating layer. [5] The aluminum fin material according to any one of [1] to [4], further comprising a base treatment layer between the aluminum plate and the coating layer.

[0014] [6] An anti-frost agent comprising an amphoteric polylysine derivative. [7] The icing and frosting inhibitor according to [6], wherein the anionic group of the amphoteric polylysine derivative has the following structure in a side chain:

[0015] [ka]

[0016] (In the formula, R represents a direct bond or a linear or branched alkylene group having 1 to 5 carbon atoms.) Effect of the Invention

[0017] According to the present invention, the condensation water adhering to the fin material surface interacts with the frost-suppressing coating layer to suppress ice nucleation. As a result, it is possible to provide an aluminum fin material in which the freezing of the condensation water is delayed and frost formation on the surface is suitably suppressed. In addition, the icing and frosting suppression effect can be exerted not only on aluminum fin materials, but also on other materials. That is, the present invention can provide an icing and frosting suppression agent that can be applied to, for example, aircraft, vinyl greenhouses, power generation turbines, etc. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of the configuration of an aluminum fin material. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of the configuration of an aluminum fin material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, the aluminum fin material and the frost suppressant according to the present invention will be described in detail. Note that the symbol "to" indicating a range of values ​​is used to mean that the values ​​before and after the symbol are included as the lower and upper limits.

[0020] <Aluminum fin material> As shown in Fig. 1, an aluminum fin material 10 (hereinafter, sometimes simply referred to as "fin material") according to this embodiment has an aluminum plate 1 and a coating layer 2 formed on the surface of the aluminum plate 1. The coating layer 2 includes an icing / frosting suppression coating layer 2a containing an amphoteric polylysine derivative.

[0021] The coating layer 2 may further include at least one selected from the group consisting of a corrosion-resistant coating layer, a hydrophilic coating layer, and a lubricating coating layer. When all of these coating layers are included, for example, as shown in FIG. 2, the coating layers are provided in the order of a corrosion-resistant coating layer 2b, a hydrophilic coating layer 2c, and a lubricating coating layer 2d from the aluminum plate 1 side.

[0022] 2, the ice / frost suppression coating layer 2a is located between the hydrophilic coating layer 2c and the lubricating coating layer 2d, but the location of the ice / frost suppression coating layer 2a is not limited thereto. That is, the ice / frost suppression coating layer 2a may be provided between the aluminum plate 1 and the corrosion-resistant coating layer 2b, between the corrosion-resistant coating layer 2b and the hydrophilic coating layer 2c, between the hydrophilic coating layer 2c and the lubricating coating layer 2d, or as the outermost layer.

[0023] Furthermore, the ice / frost-suppressing coating layer 2a may also function as the hydrophilic coating layer 2c. Although details will be described later, for example, by further including a crosslinking agent in the ice / frost-suppressing coating layer 2a, the hydrophilic effect can be more suitably obtained, and an ice / frost-suppressing coating layer can be formed that combines the function of a hydrophilic coating layer with the function of suppressing ice / frost.

[0024] A base treatment layer may further be provided between the aluminum plate 1 and the coating layer 2. Furthermore, it is sufficient that at least one surface of the aluminum plate 1 has the above configuration, and both surfaces of the aluminum plate 1 may have the above configuration. Furthermore, when both surfaces of the aluminum plate 1 have the above configuration, both surfaces do not need to have the same configuration.

[0025] (Ice and frost prevention coating layer) The frost-suppressing coating layer 2a contains an amphoteric polylysine derivative. The amphoteric polylysine derivative is an amphoteric polymer derived from polylysine having a cationic group and an anionic group. Polylysine is a polymer having the following structure as a repeating unit. Only one type of amphoteric polylysine derivative may be used, or two or more types may be used.

[0026] [ka]

[0027] The amphoteric polylysine derivative is composed of a cationic group in which the amino group of the polylysine is positively charged, and an anionic group in which the amino group of the polylysine is negatively charged by introducing an anionic group thereinto. By using an amphoteric polylysine derivative having an anionic group and a cationic group in one molecule, precipitation does not occur, which is preferable in terms of solution stability of the coating composition, as compared with a mixture of an anionic compound and a cationic compound.

[0028] The polar group portion of the cationic group of the amphoteric polylysine derivative is -N + R 1 R 2 R 3 It is expressed as R 1 ~R 3 are each independently a hydrogen atom or a linear or branched alkyl group having 1 to 5 carbon atoms. 1 ~R 3 are preferably both hydrogen atoms.

[0029] The polar group portion of the anionic group of the amphoteric polylysine derivative is -COO - , -SO3 - , -PO 3- Among them, from the viewpoint of obtaining materials, - is preferred.

[0030] In order to obtain a better anti-frosting effect, it is preferable that the anionic group has the following structure on the side chain: In the formula, R represents a direct bond or a linear or branched alkylene group having 1 to 5 carbon atoms. R is more preferably a direct bond or a linear alkylene group having 1 or 2 carbon atoms, and further preferably a linear alkylene group having 1 or 2 carbon atoms. Also, R is more preferably a branched alkylene group having 3 to 5 carbon atoms, and even more preferably a branched alkylene group having 4 or 5 carbon atoms. In the case of a branched alkylene group, it may have multiple branch chains, for example, R may be a dialkyl alkylene group such as a 1,1-dimethylethylene group or a 1-ethyl-2-methyl-ethylene group. It may also be an alkylene group with a longer branch chain, for example, R may be a methylene group having an ethyl group, propyl group, or butyl group as a side chain, or an ethylene group having a propyl group as a side chain.

[0031] [ka]

[0032] The method for producing the amphoteric polylysine derivative is not particularly limited. For example, an amphoteric polylysine derivative having an anionic group having a carboxyl group in the side chain can be obtained by reacting ε-polylysine with an acid anhydride. The acid anhydride is not particularly limited, but examples thereof include succinic anhydride, glutaric anhydride, 3,3-dimethylglutaric anhydride, butylsuccinic anhydride, acetic anhydride, citric anhydride, malic anhydride, phthalic anhydride, and maleic anhydride.

[0033] The frost formation suppression effect can be adjusted by the amount of anhydrous acid added, i.e., the ratio of cationic groups to anionic groups. A preferred amount of anhydrous acid added cannot be generally defined because it varies depending on the type of anhydrous acid used, the concentration and molecular weight of ε-polylysine, etc., but for example, the carboxylation rate is preferably 5 mol% or more, more preferably 20 mol% or more, even more preferably 40 mol% or more, and is preferably 95 mol% or less, more preferably 75 mol% or less.

[0034] The anti-frost coating layer preferably contains a crosslinking agent in addition to the amphoteric polylysine derivative from the viewpoint of enhancing hydrophilicity. Any crosslinking agent known in the art can be used, including, for example, crosslinking agents containing an oxazoline group, an oxiranyl group (1,2-epoxy structure), an oxetanyl group (1,3-epoxy structure), an isocyanate group, a blocked isocyanate group, etc. Among these, an oxazoline group and an oxiranyl group are more preferred. When sufficient hydrophilicity is obtained by containing a crosslinking agent, the frost-preventing coating layer can also function as a hydrophilic coating layer without providing a separate hydrophilic coating layer on the fin material.

[0035] In addition to the amphoteric polylysine derivative, the anti-frost coating layer preferably further contains a surfactant in order to enhance hydrophilicity. By containing a surfactant, even if the fin material further includes a lubricating coating layer, the workability and hydrophilicity of the lubricating coating layer can be more preferably achieved at the same time. This is believed to be due to the exposing action of the surfactant.

[0036] The surfactant may be any of anionic, cationic and nonionic types, but nonionic surfactants are preferred from the viewpoint of ease of dispersion in the anti-frost coating layer.

[0037] Examples of the anionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkyl ether phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl sulfosuccinates, and polyoxyethylene polyoxypropylene block copolymers.

[0038] Examples of nonionic surfactants include ethylenediamine polyoxypropylene-polyoxyethylene condensates, polyoxyethylene sorbitan monolaurate, polyoxyethylene polyoxypropylene block polymers, polyoxyethylene sorbitan monostearate, and the like.

[0039] The anti-icing / frosting coating layer can be formed by applying a coating composition containing an amphoteric polylysine derivative onto an aluminum plate or layer on which the anti-icing / frosting coating layer is to be formed, and solidifying the composition by drying or the like. The content of the amphoteric polylysine derivative in the frost-suppressing coating layer is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, in terms of solid content ratio. The upper limit of the content is not particularly limited, and the solid content ratio may be 100% by mass, i.e., the layer may be composed of only the amphoteric polylysine derivative.

[0040] When the frost-suppressing coating layer contains a crosslinking agent, the content of the crosslinking agent relative to 100 parts by mass of the amphoteric polylysine derivative is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, in terms of solid content ratio.

[0041] When the frost-suppressing coating layer contains a surfactant, the content of the surfactant relative to 100 parts by mass of the amphoteric polylysine derivative is, in terms of solid content ratio, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less.

[0042] The amount of the anti-icing / frosting coating layer is 0.01 g / m2 in order to obtain a sufficient anti-icing / frosting effect. 2 More than 0.1 g / m is preferable. 2 More preferably, the coating amount of the anti-frost coating layer is 5 g / m. 2 Less than 3 g / m is preferred. 2 The following is more preferred:

[0043] The anti-frost coating layer may contain other optional components within the scope of the present invention, such as various water-based solvents and paint additives for improving the paintability, workability, and physical properties of the coating layer. Examples of paint additives include water-soluble organic solvents, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, anti-fungal agents, etc. These paint additives may be contained alone or in combination of two or more.

[0044] The thickness of the anti-icing / frosting coating layer is not particularly limited, but the density of the anti-icing / frosting coating layer is preferably 1 g / cm 3 Assuming this, in order to obtain good frost formation suppression properties, the thickness is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 0.3 μm or more. There is no particular upper limit, but the thickness is preferably 5 μm or less, and more preferably 3 μm or less. The thickness of the anti-icing / frosting coating layer can be adjusted by the concentration of the coating composition used to form the anti-icing / frosting coating layer, the selection of the bar coater number, and the like.

[0045] (Aluminum plate) The aluminum plate is a concept that includes a plate made of aluminum and a plate made of an aluminum alloy, and an aluminum plate that has been conventionally used for aluminum fin materials can be used. As the aluminum plate, 1000 series aluminum as specified in JIS H 4000:2014 is preferable because of its excellent thermal conductivity and workability. More specifically, aluminum alloy numbers 1050, 1070, and 1200 are more preferable as the aluminum plate. However, the above description does not exclude the use of 2000 series to 9000 series aluminum alloys or other aluminum plates as the aluminum plate.

[0046] The aluminum plate is made to have a desired thickness depending on the application and specifications of the fin material. For fin materials for heat exchangers, the thickness is preferably 0.08 mm or more, more preferably 0.1 mm or more, from the viewpoint of the strength of the fin. On the other hand, the thickness is preferably 0.3 mm or less, more preferably 0.2 mm or less, from the viewpoint of the workability into fins and the heat exchange efficiency.

[0047] (Corrosion-resistant coating layer) The corrosion-resistant coating layer is a layer formed on the aluminum plate mainly for the purpose of increasing the corrosion resistance of the aluminum plate, and preferably contains a hydrophobic resin. When a base treatment layer is formed on the surface of the aluminum plate, the corrosion-resistant film layer is formed on the base treatment layer. Also, when an anti-icing / frosting film layer is formed on the aluminum plate or on the base treatment layer, the corrosion-resistant film layer may be formed on the anti-icing / frosting film layer. The corrosion-resistant coating layer can be formed, for example, by applying a coating composition containing a hydrophobic resin onto an aluminum plate, a substrate treatment layer, or an anti-frost coating layer, and then solidifying the coating by drying or the like.

[0048] The corrosion-resistant coating layer makes it difficult for moisture such as condensation water, oxygen, chloride ions and other ionic species to penetrate the aluminum plate, thereby suppressing corrosion of the aluminum plate and the production of odorous aluminum oxides.

[0049] The hydrophobic resin in the corrosion-resistant coating layer may be a conventionally known resin, such as polyester, polyolefin, melamine, epoxy, urethane, or acrylic resin, or a mixture of two or more of these resins.

[0050] In addition to the above, the corrosion-resistant coating layer may contain other optional components within the range that does not impair the effects of the present invention. Examples of optional components include various water-based solvents and paint additives for improving the paintability, workability, and physical properties of the coating. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surfactants, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, antifungal agents, etc. These paint additives may be contained alone or in combination of two or more.

[0051] The amount of the hydrophobic resin in the corrosion-resistant coating layer is not particularly limited. From the viewpoint of imparting sufficient corrosion resistance to the aluminum plate, the amount of the hydrophobic resin is preferably 0.05 g / m 2 More than 0.2 g / m is preferable. 2On the other hand, from the viewpoint of suppressing the decrease in the heat exchange efficiency of the fins, the adhesion amount of the hydrophobic resin is set to 15 g / m 2 Less than 3 g / m is preferred. 2 The following is more preferred: The thickness of the corrosion-resistant coating layer is preferably 0.05 μm or more from the viewpoint of obtaining good corrosion resistance, and is preferably 15 μm or less from the viewpoints of good film-forming properties, reduced defects such as cracks, low heat transfer resistance of the corrosion-resistant coating layer, and good heat exchange efficiency of the fin. The thickness of the corrosion-resistant film layer and the amount of hydrophobic resin applied can be adjusted by the concentration of the coating composition used to form the corrosion-resistant film layer and the selection of the bar coater number.

[0052] (Hydrophilic film layer) The hydrophilic coating layer is a coating layer that imparts hydrophilicity to the surface of the fin material, and contains a conventionally known hydrophilic resin. The hydrophilic resin may contain one type of resin or two or more types of resins as long as it has a hydrophilic group. Examples of the hydrophilic group include a hydroxyl group, a carboxyl group, a sulfonic acid group, and a polyether group.

[0053] Examples of those having a hydroxyl group include polyethylene glycol (PEG) and polyvinyl alcohol (PVA). Examples of those having a carboxyl group include polyacrylic acid (PAA). Examples of those having a hydroxyl group and a carboxyl group include carboxymethyl cellulose (CMC). Examples of those having a sulfonic acid group include sulfoethyl acrylate. Examples of those having a polyether group include polyethylene glycol (PEG) and modified compounds thereof.

[0054] Among these, from the viewpoint of more suitably exhibiting the desired hydrophilicity even when a lubricating coating layer is formed on the surface of the hydrophilic coating layer, the hydrophilic resin is preferably one containing a sulfonic acid group or a polyether group, i.e., one containing an ether bond, more preferably one containing a sulfonic acid group and an ether bond, and particularly preferably an acrylic acid resin containing a sulfonic acid group and an ether bond.

[0055] The acrylic acid resin containing sulfonic acid and an ether bond is an acrylic acid resin containing an unsaturated double bond group and a sulfonic acid group, and examples thereof include polyvinyl ether-sulfonic acid acrylic copolymer, benzyl ether-sulfonic acid acrylic copolymer, etc. However, the acrylic acid resin containing sulfonic acid and an ether bond is not limited to these.

[0056] In addition to the above, the hydrophilic resin may be a copolymer of two or more monomers having a hydrophilic group. For example, a copolymer of acrylic acid and sulfoethyl acrylate may be used. The copolymer may be an alternating copolymer, a block copolymer, a graft copolymer, a random copolymer, or the like, and the arrangement of the monomers is not particularly limited.

[0057] It is preferable that the hydrophilic coating layer further contains a surfactant in addition to the hydrophilic resin. This allows for both better hydrophilicity and workability due to the lubricating coating layer formed on the hydrophilic coating layer. This is believed to be due to the exposure action of the surfactant.

[0058] The surfactant may be any of anionic, cationic and nonionic types, but nonionic surfactants are preferred from the viewpoint of ease of dispersion in the hydrophilic coating layer.

[0059] Examples of nonionic surfactants include ethylenediamine polyoxypropylene-polyoxyethylene condensates, polyoxyethylene sorbitan monolaurate, polyoxyethylene polyoxypropylene block polymers, polyoxyethylene sorbitan monostearate, and the like.

[0060] The hydrophilic coating layer can be formed by applying a coating composition containing a hydrophilic resin onto a corrosion-resistant coating layer when the coating composition is formed thereon, and solidifying the coating composition by drying, etc. When an ice / frost-suppressing coating layer is formed on a corrosion-resistant coating layer, the hydrophilic coating layer is formed by applying a coating composition onto the ice / frost-suppressing coating layer, and solidifying the coating composition by drying, etc. The amount of hydrophilic resin attached to the hydrophilic film is 0.05 g / m2 in order to obtain sufficient hydrophilicity. 2 More than 0.1 g / m is preferable. 2 More preferably, 0.2 g / m or more 2 More preferably, the amount of the hydrophilic resin is 5 g / m or more. From the viewpoint of preventing the hydrophilic resin from being dissolved when the surface of the fin material becomes wet with water, which would impair the effect of the lubricating coating layer, the amount of the hydrophilic resin attached is preferably 5 g / m or more. 2 Less than 3 g / m is preferred. 2 Less than 1 g / m is more preferable. 2 The following is even more preferred:

[0061] In addition to the hydrophilic resin and surfactant, the hydrophilic coating layer may contain other optional components within the range that does not impair the effects of the present invention. Examples of the optional components include various water-based solvents and paint additives for improving the coatability, workability, and physical properties of the coating layer. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, antifungal agents, etc. These paint additives may be contained alone or in combination of two or more.

[0062] The thickness of the hydrophilic coating layer is not particularly limited, but the density of the hydrophilic coating layer is preferably 1 g / cm 3 Assuming this, in order to obtain good hydrophilicity, the thickness is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more. Also, in order to obtain good coating workability when forming the hydrophilic coating layer, the thickness is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. The thickness of the hydrophilic coating layer can be adjusted by the concentration of the coating composition used to form the hydrophilic coating layer, the selection of the bar coater number, and the like.

[0063] In addition, when the fin material has a hydrophilic coating layer and a lubricating coating layer in addition to the frost-preventing coating layer, the total thickness of these layers is preferably 5 μm or less in order to prevent a decrease in the heat exchange efficiency of the fin material.

[0064] (lubricating coating layer) The lubricating coating layer is a layer intended to obtain good processability by increasing the lubricity of the fin material surface, and contains a conventionally known resin that increases lubricity. This reduces the friction coefficient of the fin material surface, making it lubricated, and improves press formability when processing the fin material into a fin.

[0065] Examples of resins that enhance lubricity include resins having hydrophilic groups, such as hydroxyl groups, carboxyl groups, sulfonic acid groups, and polyether groups.

[0066] Examples of resins having hydroxyl groups include polyethylene glycol (PEG) and polyvinyl alcohol (PVA). Examples of resins having carboxyl groups include polyacrylic acid (PAA). Examples of resins having hydroxyl and carboxyl groups include carboxymethyl cellulose (CMC). Examples of resins having sulfonic acid groups include sulfoethyl acrylate. Examples of resins having polyether groups include polyethylene glycol (PEG) and modified compounds thereof. In addition to these, copolymers of two or more types of monomers having hydrophilic groups can also be used.

[0067] In addition to the above, the lubricating coating layer may contain other optional components within the scope of the invention, such as various water-based solvents and paint additives for improving the coatability, workability, and physical properties of the coating layer. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surfactants, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, antifouling agents, rust inhibitors, antibacterial agents, antifungal agents, etc. These paint additives may be contained alone or in combination of two or more.

[0068] The lubricating coating layer can be formed by applying a coating composition containing a resin that enhances lubricity, such as a resin having a hydroxyl group, onto the hydrophilic coating layer and solidifying it by drying, etc. In addition, when there is no hydrophilic coating layer or when an anti-icing / frosting coating layer is formed, the lubricating coating layer is formed on the layer below it or on the anti-icing / frosting coating layer.

[0069] The amount of the lubricating coating layer is 0.05 g / m2 to obtain sufficient lubricity. 2 More than 0.1 g / m is preferable. 2 More preferably, 0.2 g / m or more 2 More preferably, the coating amount is 5 g / m or more. On the other hand, the upper limit is not particularly limited, but the coating amount is preferably 5 g / m 2 Less than 3 g / m is preferred. 2 Less than 1 g / m is more preferable. 2 The following is even more preferred:

[0070] The thickness of the lubricating coating layer is not particularly limited, but from the viewpoint of obtaining good lubricity, the density of the coating layer is set to 1 g / cm 3 Assuming this, the thickness is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more. Although there is no particular upper limit, the thickness is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. The thickness of the lubricating coating layer can be adjusted by the concentration of the coating composition used to form the lubricating coating layer, the selection of the bar coater number, and the like.

[0071] (Base treatment layer) A primer layer may optionally be provided on the aluminum plate. By providing a base treatment layer, the corrosion resistance of the aluminum plate can be increased, and when a corrosion-resistant coating layer is further provided, the adhesion between the aluminum plate and the corrosion-resistant coating layer can be increased.

[0072] The undercoat treatment layer may be any layer that can impart corrosion resistance to the aluminum plate, and may be any layer known in the art, such as a layer made of an inorganic oxide or an inorganic-organic composite compound. As the inorganic material constituting the inorganic oxide or inorganic-organic composite compound, chromium (Cr), zirconium (Zr) or titanium (Ti) is preferred as the main component.

[0073] The layer made of an inorganic oxide that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to a chromate phosphate treatment, a zirconium phosphate treatment, a zirconium oxide treatment, a chromate chromate treatment, a zinc phosphate treatment, a titanic acid phosphate treatment, etc. However, the type of inorganic oxide is not limited to those formed by these treatments.

[0074] The layer made of an inorganic-organic composite compound that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to coating-type chromate treatment, coating-type zirconium treatment, etc. Specific examples of such inorganic-organic composite compounds include, for example, acrylic-zirconium composites.

[0075] The thickness of the undercoat treatment layer is not particularly limited and may be set appropriately, but the amount of adhesion per unit area is preferably 1 to 100 mg / m in terms of metal (Cr, Zr, Ti). 2 The thickness of the film is preferably 1 to 100 nm. The deposition amount and film thickness of the undercoat treatment layer can be adjusted by adjusting the concentration of the chemical conversion treatment solution used in forming the undercoat treatment layer and the film formation treatment time.

[0076] Before forming the primer layer, the surface of the aluminum plate may be degreased in advance using an alkaline degreasing solution, which improves the reactivity of the primer treatment and also improves the adhesion of the formed primer layer.

[0077] (Characteristics of aluminum fin material) In the aluminum fin material according to the present embodiment, even if condensed water adheres to the surface, the condensed water interacts with the frost-suppressing coating layer to suppress ice nucleation. As a result, the freezing of the condensed water is delayed, and frost formation on the surface of the fin material can be appropriately suppressed.

[0078] The frost suppression effect of the fin material can be evaluated by the following method. A copper plate equipped with a refrigerant flow path, a Peltier element, and an air flow path is placed on the upper inside of an acrylic cylinder, and the device is placed in an environment with a temperature of 10°C and a relative humidity of 55%. A fin material is placed on the copper plate at a position where it comes into contact with the air inside the cylinder. Then, air is blown into the cylinder at a speed of 1.5 m / s. After the above process, the copper plate is cooled while continuing to blow air into the tube at the same air speed, the surface temperature is set to -7.5°C, and condensation water is intentionally formed on the surface of the fin material. A digital microscope is installed on the side of the fin material where the condensation water adheres, and the state of the condensation water and frost on the fin material surface is observed. The time from the start of cooling to the start of frost formation is measured as the "frost formation delay time" and the frost formation suppression effect is evaluated. The frost formation delay time according to the above method is preferably 15 minutes or more, more preferably 30 minutes or more.

[0079] Hydrophilicity is also an important parameter when using fin materials in heat exchangers. Therefore, when a fin material is provided with a hydrophilic coating layer or when a crosslinking agent is added to an anti-frost coating layer to improve hydrophilicity, the hydrophilicity can be evaluated by the contact angle when pure water is dropped on the surface of the fin material. Specifically, about 2 μL of pure water is dropped onto the surface of the fin material at room temperature, and the contact angle of the droplet (pure water) is measured using a contact angle measuring device. The contact angle of the droplet (pure water) is preferably less than 60°, more preferably less than 40°, and even more preferably less than 20°. The lower limit is not particularly limited, but is usually 5° or more.

[0080] As the durability of the hydrophilicity of the fin material, the fin material is immersed in pure water for 8 hours, dried at 80°C for 3 hours, and then returned to room temperature, and the contact angle of the liquid droplet (pure water) is measured in the same manner as above. The contact angle of the liquid droplet (pure water) is preferably less than 60°, more preferably less than 40°, and even more preferably less than 20°. The lower limit is not particularly limited, but is usually 5° or more.

[0081] <Method of manufacturing aluminum fin material> An example of a manufacturing method for the aluminum fin material according to this embodiment will be described, but the present invention is not limited to this embodiment, and other manufacturing methods can also be used as long as they do not interfere with the effects of this embodiment. In addition, the following example describes a case where a base treatment layer, a corrosion-resistant film layer, a hydrophilic film layer, an anti-icing / frosting film layer, and a lubricating film layer are formed in this order on the surface of an aluminum plate, but the formation of the base treatment layer, the corrosion-resistant film layer, the hydrophilic film layer, and the lubricating film layer is not essential but is optional. In addition, the position where the anti-icing / frosting film layer is formed is not limited to between the hydrophilic film layer and the lubricating film layer, and it can be formed at any position.

[0082] A base treatment layer is formed on the surface of an aluminum plate by a known method, and a corrosion-resistant coating layer is then formed on the surface by a known method, followed by coating a coating composition containing a hydrophilic resin, drying, and baking to form a hydrophilic coating layer.

[0083] Next, a coating composition containing an amphoteric polylysine derivative is applied onto the hydrophilic coating layer, dried, and baked to form an anti-frost coating layer. The coating composition containing the amphoteric polylysine derivative may contain other components such as a crosslinking agent and a surfactant. By containing a crosslinking agent, better hydrophilicity can be achieved in addition to the effect of suppressing frost formation. Furthermore, by containing a surfactant, even if the fin material further comprises a lubricating coating layer, the workability due to the lubricating coating layer, the frost formation suppression property and the hydrophilicity can be more preferably achieved at the same time.

[0084] The solvent of the coating composition containing the amphoteric polylysine derivative is not particularly limited, and examples thereof include water, alcohol, aliphatic ketones, etc. Among them, water and alcohol are preferred, and as the alcohol, butanol, ethanol, etc. are preferred. The solvent may be used alone or in combination of two or more. For example, in the case of a mixed solvent of water and alcohol, it is preferable from the viewpoint of coatability onto a substrate that the amount of alcohol is 1 to 20 parts by mass per 100 parts by mass of water.

[0085] The solid content concentration in the coating composition containing the amphoteric polylysine derivative is preferably % by mass or more, more preferably 1% by mass or more, and even more preferably 3% by mass or more, from the viewpoint of coating stability, and is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, from the viewpoint of coatability on a substrate.

[0086] The thickness of the coating film when the coating composition containing the amphoteric polylysine derivative is applied is preferably 1 μm or more, more preferably 5 μm or more, from the viewpoint of coatability. Also, the thickness of the coating film is preferably 40 μm or less, more preferably 20 μm or less, from the viewpoint of volatility of the solvent. Note that the thickness here is the thickness before drying, and when the coating composition is applied using a bar coater, for example, it can be adjusted by selecting the bar coater number.

[0087] Next, for example, a coating composition containing a resin having a hydrophilic group is applied onto the surface of the frost-preventing coating layer, and then dried and baked to form a lubricating coating layer. The baking temperature is not particularly limited as long as the anti-icing / frosting coating layer can be formed without peeling, but is preferably 100° C. or higher, and more preferably 200° C. or higher. From the viewpoint of preventing oxidation of the resin of the anti-icing / frosting coating layer, the baking temperature is preferably 400° C. or lower, and more preferably 300° C. or lower. The above baking temperature is the temperature of the oven in which the baking is performed. The baking time is not particularly limited as long as the anti-icing / frosting coating layer can be formed without peeling, but is preferably 3 seconds or more, more preferably 10 seconds or more, and is preferably 2 hours or less, more preferably 1 hour or less, from the viewpoint of preventing oxidation of the resin of the anti-icing / frosting coating layer.

[0088] The application of the corrosion-resistant coating layer, the hydrophilic coating layer, the anti-frost coating layer, and the lubricating coating layer is carried out by a bar coater, a roll coating method, etc. In particular, when the aluminum plate is in a coil shape, it is preferable in terms of productivity to continuously carry out degreasing, painting, heating, winding, etc. using a roll coating device, etc. In addition, the baking temperature of the corrosion-resistant coating layer, the hydrophilic coating layer, and the lubricating coating layer may be set according to the components of the resin, etc., respectively used, and is preferably in the range of, for example, 120 to 270 ° C.

[0089] <Icing and frost suppressant> The anti-frosting agent according to the present embodiment contains an amphoteric polylysine derivative. The amphoteric polylysine derivative may be the same as that described in the above <Aluminum Fin Material> (Anti-frosting Coating Layer), and the preferred aspects are also the same. In addition, the components other than the amphoteric polylysine derivative contained in the icing and frosting inhibitor are the same as the components other than the amphoteric polylysine derivative contained in the (icing and frosting suppression coating layer) of the above-mentioned <aluminum fin material>, and the preferred aspects are also the same. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples, and can be practiced with modifications within the scope of the invention, all of which are included in the technical scope of the present invention.

[0091] (Synthesis of amphoteric polylysine derivative A-1) Glutaric anhydride (GA) was added at 50 mol% to the amino groups of ε-poly-L-lysine (manufactured by JNC Corporation, 25% aqueous solution, weight average molecular weight approximately 4000) and reacted at 50° C. for 2 hours to obtain amphoteric polylysine derivative A-1 represented by the following structural formula. This was a polymer with a carboxylation rate of 50% and was neutral, so it was dried as it was and powdered.

[0092] [ka]

[0093] (Synthesis of amphoteric polylysine derivative A-2) Amphoteric polylysine derivative A-2 represented by the following structural formula was obtained in the same manner as in the synthesis of amphoteric polylysine derivative A-1, except that 3,3-dimethylglutaric anhydride (DMGA) was used instead of glutaric anhydride. Since this was a polymer with a carboxylation rate of 50% and was neutral, it was dried as it was and powdered.

[0094] [ka]

[0095] (Synthesis of amphoteric polylysine derivative A-3) Amphoteric polylysine derivative A-3 was obtained in the same manner as in the synthesis of amphoteric polylysine derivative A-2, except that the amount of 3,3-dimethylglutaric anhydride (DMGA) added was 65 mol% relative to the amino group of ε-poly-L-lysine. The structural formula of amphoteric polylysine derivative A-3 is the same as that of amphoteric polylysine derivative A-2. Since the amphoteric polylysine derivative A-3 had a carboxylation rate of 65%, it was neutralized with a 5M NaOH solution, dried, and powdered.

[0096] (Synthesis of amphoteric polylysine derivative A-4) Amphoteric polylysine derivative A-4 represented by the following structural formula was obtained in the same manner as in synthesis of amphoteric polylysine derivative A-1, except that succinic anhydride (SA) was used instead of glutaric anhydride and the amount of SA added was 65 mol% relative to the amino groups of ε-poly-L-lysine. Since this had a carboxylation rate of 65%, it was neutralized with 5M NaOH solution, dried, and powdered.

[0097] [ka]

[0098] (Synthesis of amphoteric polylysine derivative A-5) Amphoteric polylysine derivative A-5 was obtained in the same manner as in the synthesis of amphoteric polylysine derivative A-4, except that the amount of succinic anhydride (SA) added was 50 mol% relative to the amino group of ε-poly-L-lysine. Since this is a polymer with a carboxylation rate of 50% and is neutral, it was dried as it is and powdered. The structural formula of amphoteric polylysine derivative A-5 is the same as that of amphoteric polylysine derivative A-4.

[0099] Example 1 The aluminum plate used was an aluminum plate having a thickness of 0.1 mm and a standard of alloy number 1070 as specified in JIS H 4000: 2014. A primer layer was formed on one surface of the aluminum plate by phosphate chromate treatment. Next, a coating composition containing the synthesized amphoteric polylysine derivative A-1 was prepared using water as a solvent. る The solid content concentration was 5% by mass. This coating composition was applied to the surface of an aluminum plate to a thickness of 9 μm using a bar coater. It was then dried and baked at 280° C. to form an anti-icing / frosting coating layer, and an aluminum fin material was obtained. The coating amount of the anti-icing / frosting coating layer was 1.20 g / m 2 It was.

[0100] Example 2 A coating composition was prepared using water as a solvent, containing the synthesized amphoteric polylysine derivative A-3 and an oxazoline group-containing polymer as a crosslinking agent B-1. The amount of crosslinking agent B-1 added per 100 parts by mass of amphoteric polylysine derivative A-3 was 5 parts by mass in terms of solid content concentration. The solid content concentration in the coating composition was 5% by mass. This coating composition was applied to the surface of the same aluminum plate as used in Example 1 with a bar coater to a thickness of 7 μm. The coating was then dried and baked at 280° C. to form an anti-icing / frosting coating layer, and an aluminum fin material was obtained. The coating amount of the anti-icing / frosting coating layer was 0.13 g / m 2 It was.

[0101] Example 3 A coating composition containing the synthesized amphoteric polylysine derivative A-2 and polyethylene glycol diglycidyl ether as crosslinking agent B-2 was prepared using water as a solvent. The amount of crosslinking agent B-2 added per 100 parts by mass of amphoteric polylysine derivative A-2 was 5 parts by mass in terms of solid content concentration. The solid content concentration in the coating composition was 5% by mass. This coating composition was applied to the surface of the same aluminum plate as used in Example 1 with a bar coater to a thickness of 7 μm. The coating was then dried and baked at 280° C. to form an anti-icing / frosting coating layer, and an aluminum fin material was obtained. The coating amount of the anti-icing / frosting coating layer was 0.24 g / m 2 It was.

[0102] Example 4 An aluminum fin material was obtained in the same manner as in Example 3, except that the amphoteric polylysine derivative A-5 was used instead of the amphoteric polylysine derivative A-2. The coating amount of the frost-preventing coating layer was 0.06 g / m 2 It was.

[0103] Example 5 An aluminum fin material was obtained in the same manner as in Example 3, except that the amphoteric polylysine derivative A-4 was used instead of the amphoteric polylysine derivative A-2. The coating amount of the frost-preventing coating layer was 0.13 g / m 2 It was.

[0104] Example 6 An aluminum fin material was obtained in the same manner as in Example 5, except that the solid content concentration in the coating composition was 30 mass %.

[0105] Example 7 An aluminum fin material was obtained in the same manner as in Example 5, except that the solid content concentration in the coating composition was 10 mass % and the coating thickness using a bar coater was 9 μm. The coating amount of the anti-frost coating layer was 0.59 g / m 2 It was.

[0106] Example 8 A coating composition was prepared using water as a solvent, containing the synthesized amphoteric polylysine derivative A-4, polyethylene glycol diglycidyl ether as crosslinking agent B-2, and polyoxyethylene alkyl ether as surfactant C-1 (manufactured by Kao Corporation, Emulgen 705). The amounts of crosslinking agent B-2 and surfactant C-1 added per 100 parts by mass of amphoteric polylysine derivative A-4 were 5 parts by mass and 1 part by mass, respectively, in terms of solid content concentration ratio. The solid content concentration in the coating composition was 5% by mass. This coating composition was applied to a thickness of 7 μm using a bar coater onto the surface of the same aluminum plate as used in Example 1. The coating was then dried and baked at 280° C. to form an anti-frost coating layer, thereby obtaining an aluminum fin material.

[0107] Example 9 An aluminum fin material was obtained in the same manner as in Example 8, except that the surfactant was changed from C-1, polyoxyethylene alkyl ether, to C-2, polyoxyethylene polyoxypropylene block copolymer (manufactured by Sanyo Chemical Industries, Ltd., Newpol PE-64).

[0108] Example 10 An aluminum fin material was obtained in the same manner as in Example 8, except that the surfactant was changed from C-1 polyoxyethylene alkyl ether to C-3 ethylenediamine polyoxypropylene-polyoxyethylene condensate (ADEKA CORPORATION, Pluronic TR-913R).

[0109] Example 11 A coating composition was prepared using water:butanol=100:5 (mass ratio) as a solvent, containing the synthesized amphoteric polylysine derivative A-4, polyethylene glycol diglycidyl ether as crosslinking agent B-2, and polyoxyethylene polyoxypropylene block copolymer as surfactant C-2 (Newpol PE-64, manufactured by Sanyo Chemical Industries, Ltd.). The amounts of crosslinking agent B-2 and surfactant C-2 added per 100 parts by mass of amphoteric polylysine derivative A-4 were 5 parts by mass and 1 part by mass, respectively, in terms of solid content concentration ratio. The solid content concentration in the coating composition was 3.7% by mass. This coating composition was applied to a thickness of 9 μm using a bar coater onto the surface of the same aluminum plate as used in Example 1. The coating was then dried and baked at 280° C. to form an anti-frost coating layer, thereby obtaining an aluminum fin material.

[0110] Example 12 An aluminum fin material was obtained in the same manner as in Example 11, except that the solid content concentration in the coating composition was 5 mass %.

[0111] (Example 13) An aluminum fin material was obtained in the same manner as in Example 11, except that the solid content concentration in the coating composition was 10 mass %.

[0112] Example 14 An aluminum fin material was obtained in the same manner as in Example 5, except that a corrosion-resistant coating layer was formed between the aluminum plate and the frost-preventing coating layer. The corrosion-resistant coating layer was formed by applying a coating composition containing a polyvinyl alcohol-polyvinylpyrrolidone copolymer and a melamine resin onto the surface of an aluminum plate, drying it, and baking it at 280°C. The total coating weight of the anti-icing / frosting coating layer and the corrosion-resistant coating layer was 0.69 g / m 2 It was.

[0113] Example 15 An aluminum fin material was obtained in the same manner as in Example 5, except that a hydrophilic coating layer was formed between the aluminum plate and the frost-preventing coating layer. The hydrophilic coating layer was formed by applying a coating composition containing sodium silicate onto the surface of an aluminum plate, drying it, and baking it at 280°C. The total coating weight of the anti-icing / frosting coating layer and the hydrophilic coating layer was 1.25 g / m 2 It was.

[0114] Example 16 An aluminum fin material was obtained in the same manner as in Example 9, except that the solids concentration in the paint composition that would become the anti-icing / frosting coating layer was 10 mass%, the thickness of the coating using a bar coater was 9 μm, and a corrosion-resistant coating layer was formed between the aluminum plate and the anti-icing / frosting coating layer. The corrosion-resistant coating layer was formed by applying a coating composition containing polyacrylic acid (weight average molecular weight 250,000) and polyethylene glycol diglycidyl ether onto the surface of an aluminum plate, drying it, and baking it at 280°C. The total coating weight of the anti-icing and anti-frosting phase and the corrosion-resistant coating layer was 0.84 g / m 2 It was.

[0115] Comparative Example 1 An aluminum fin material having a hydrophilic coating layer formed on the surface thereof was obtained using an aluminum plate similar to that in Example 1. The hydrophilic coating layer used was the same as that in Example 15.

[0116] Comparative Example 2 An aluminum fin material having a corrosion-resistant coating layer formed on its surface was obtained using the same aluminum plate as in Example 1. The corrosion-resistant coating layer was formed by applying a coating composition containing polyvinyl alcohol and titanium lactate onto the surface of the aluminum plate, drying it, and baking it at 280°C.

[0117] Comparative Example 3 An aluminum fin material having a hydrophilic coating layer formed on its surface was obtained using the same aluminum plate as in Example 1. The hydrophilic coating layer was formed by applying a coating composition containing an epoxy resin onto the surface of the aluminum plate, drying it, and baking it at 280°C.

[0118] Comparative Example 4 An aluminum fin material having a hydrophilic coating layer formed on its surface was obtained using the same aluminum plate as in Example 1. The hydrophilic coating layer was formed by applying a coating composition containing modified polyacrylic acid onto the surface of the aluminum plate, drying it, and baking it at 280°C.

[0119] The configuration of the aluminum fin material obtained above is summarized in Table 1. In Table 1, "-" means that the coating layer is not formed or that the component is not added.

[0120] [Table 1]

[0121] (Evaluation: frost suppression) A copper plate equipped with a refrigerant flow path, a Peltier element, and an air flow path was placed in the upper part of the inside of an acrylic cylinder, and the device was placed in an environment of a temperature of 10°C and a relative humidity of 55%. A fin material was placed on the copper plate at a position in contact with the air inside the cylinder. Then, air was blown into the cylinder at a speed of 1.5 m / s. After the above process, the copper plate was cooled while continuing to blow air into the tube at the same air speed, the surface temperature was set to -7.5°C, and condensation water was intentionally allowed to adhere to the surface of the fin material. A digital microscope was placed on the side of the fin material where the condensation water adhered, and the state of the condensation water and frost on the fin material surface was observed. The time from the start of cooling to the start of frost formation was measured as the "frost formation delay time," and the frost formation suppression effect was evaluated. The evaluation criteria are as follows, and the results are shown in Table 2 under "Ice and frost prevention." A Very good (pass): Frost delay time is 30 minutes or more B Good (passed): Icing delay time is between 15 minutes and 30 minutes C Bad (failed): Frost delay time is less than 15 minutes

[0122] (Evaluation: Hydrophilic) At room temperature, about 2 μL of pure water was dropped onto the surface of the aluminum fin material, and the contact angle of the droplet (pure water) was measured using a contact angle meter (CA-05 model, manufactured by Kyowa Interface Science Co., Ltd.). The evaluation criteria are as follows, and the results are shown in Table 2 under "hydrophilicity." A: Very good (passed): Contact angle is less than 20° B Very good (pass): Contact angle is 20° or more and less than 40° C Good (passed): Contact angle is 40° or more and less than 60° D Poor (failed): Contact angle is 60° or more

[0123] (Evaluation: Hydrophilic durability) The obtained aluminum fin material was immersed in pure water for 16 hours, then dried at 80°C for 3 hours and returned to room temperature, after which the contact angle of a droplet (pure water) was measured in the same manner as above. The evaluation criteria are as follows, and the results are shown in "Durability (hydrophilicity)" in Table 2. In Table 2, "-" indicates that the measurement was not performed. A: Very good (passed): Contact angle is less than 20° B Very good (pass): Contact angle is 20° or more and less than 40° C Good (passed): Contact angle is 40° or more and less than 60° D Poor (failed): Contact angle is 60° or more

[0124] [Table 2]

[0125] From the above results, it was found that the formation of ice and frost suppression coating layer can be effectively suppressed. In addition, by adding a crosslinking agent or a surfactant to the ice and frost suppression coating layer, good hydrophilicity can be achieved, and in some cases, it can also function as a hydrophilic coating layer. In addition, since the durability was improved, it was confirmed that the ice and frost suppression coating layer can exert the effects of both coating layers without interfering with the effects of hydrophilic coating layers and the like that are also provided on conventional aluminum fin materials. [Explanation of symbols]

[0126] 1 Aluminum plate 2. Coating layer 2a Anti-icing film layer 2b Corrosion-resistant coating layer 2c Hydrophilic film layer 2d Lubricious film layer 10 Aluminum fin material

Claims

1. The aluminum plate has a coating layer formed on a surface of the aluminum plate. The coating layer comprises an anti-frost coating layer containing an amphoteric polylysine derivative, The aluminum fin material, wherein the anionic group of the amphoteric polylysine derivative has the following structure on its side chain: 【Chemistry 1】 (In the formula, R represents a direct bond or a linear or branched alkylene group having 1 to 5 carbon atoms.)

2. The aluminum fin material according to claim 1 , wherein the ice and frost-resistant coating layer further comprises a cross-linking agent.

3. The aluminum fin material according to claim 1 or 2, wherein the coating layer further comprises at least one selected from the group consisting of a corrosion-resistant coating layer, a hydrophilic coating layer, and a lubricating coating layer.

4. The aluminum fin material according to any one of claims 1 to 3, further comprising a base treatment layer between the aluminum plate and the coating layer.

5. Contains an amphoteric polylysine derivative, The icing and frosting inhibitor, wherein the anionic group of the amphoteric polylysine derivative has the following structure on its side chain: 【Chemistry 2】 (In the formula, R represents a direct bond or a linear or branched alkylene group having 1 to 5 carbon atoms.)

Citation Information

Patent Citations

  • Water-repelelnt member and method for preventing coating of snow and ice using the member

    JP1997228073A

  • Air conditioner, heat exchanger and its production

    JP1998281690A

  • Resin composition exhibiting high performance in inhibition of ice and frost formation, and laminated metal plate on which ice / frost-formation inhibition layer is formed

    JP2011089112A

  • Aluminum fin for heat exchanger and heat exchanger

    JP2011185590A

  • Aluminum fin material for heat exchanger

    JP2011237145A